2020
DOI: 10.1021/acs.jafc.0c05890
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Differences in Human Intestinal Microbial Conversion of (−)-Epicatechin to Bioactive Phenolic Compounds

Abstract: To quantify interindividual differences in the human intestinal microbial metabolism of (−)-epicatechin (EC), in vitro anaerobic incubations with fecal inocula from 24 healthy donors were conducted. EC-derived colonic microbial metabolites were qualitatively and quantitively analyzed by liquid chromatography triple quadrupole mass spectrometry (LC-TQ-MS) and liquid chromatography time-of-flight mass spectrometry (LC-TOF-MS). Quantitative microbiota characterization was achieved by 16S rRNA analysis. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 56 publications
(116 reference statements)
5
49
0
Order By: Relevance
“…Metabolism to succinate and propionate has been associated with improved glucose homeostasis. [ 59 , 60 ] Lachnospiraceae NC2004 [ 61 ], a genus associated with ring cleavage of polyphenolic compounds found in high-fiber foods, was also enriched after FS. Additionally, within EA, Victivallus , a cellobiose degrading bacteria, and Ruminiclostridia , a lignocellulose-degrading bacteria, were enriched after FS and may reflect higher dietary fiber, whole grains, and vegetable intake by EA in our study ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism to succinate and propionate has been associated with improved glucose homeostasis. [ 59 , 60 ] Lachnospiraceae NC2004 [ 61 ], a genus associated with ring cleavage of polyphenolic compounds found in high-fiber foods, was also enriched after FS. Additionally, within EA, Victivallus , a cellobiose degrading bacteria, and Ruminiclostridia , a lignocellulose-degrading bacteria, were enriched after FS and may reflect higher dietary fiber, whole grains, and vegetable intake by EA in our study ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is even more relevant when tentative "metabotypes" have been proposed after the analysis of in vitro or in vivo samples from a few volunteers (n1015), which is, unfortunately, the most common scenario in those studies that recurrently use the term "metabotype" in the context of (poly)phenols metabolism. 117,[128][129][130] Indeed, after analysing such small sample sizes, high and low producers could be tentatively identified by specifying an arbitrary limit to establish such a classification. However, in a large cohort, it could be possible that after applying the same cut-off, these same volunteers could be all grouped within the high producers or all of them within the low producers.…”
Section: The Qualitative Criterion: Gut Microbiota Metabotypes Associated With (Poly)phenols Metabolismmentioning
confidence: 99%
“…Many studies have demonstrated that flavonoids are extensively metabolized after absorption in the intestine (reviewed in [ 77 ]). It is also firmly established that gut microbes degrade flavonoids into a variety of metabolic products that are absorbed into the blood stream and eventually excreted [ 15 , 16 ]. These products include sulfated and glucuronidated flavonoids from enzymes in human enterocytes as well as a variety of microbial products with hydroxylated phenyl groups.…”
Section: Flavonoids May Exert Bioactivity By Forming Reversible Protein Adductsmentioning
confidence: 99%
“…These metabolic products will have different physical and chemical properties from their flavonoid parents, but it is possible that, in some cases, they could still be oxidized to electrophilic quinones. For example, the major microbial flavonoid degradation product 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone (3,4-diHPV) [ 15 ] still possesses a catechol group and therefore seems likely to be readily oxidized to a quinone. Because of the metabolic transformations that occur after passage of absorbed flavonoid from intestinal epithelium into the circulatory system, it seems probable that most of the flavonoid bioactivity will occur in these intestinal cells rather than in other tissues since the bulk of absorbed flavonoid metabolites are eventually excreted [ 16 ].…”
Section: Flavonoids May Exert Bioactivity By Forming Reversible Protein Adductsmentioning
confidence: 99%
See 1 more Smart Citation